Surrogate Mother Validity against Children’s Civil Status: Comparative Study, Surrogate Mother in Indonesia and Ukraine - Adinda Permana Putri; Dwi Aryanti Ramadhani (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
Nowadays, technology is getting more advanced.  For example, IVF or "In Vitro Fertilization (IVF)" with a surrogate mother. A surrogate mother is a woman who has no relationship at all with a spouse who owns the seed then makes an agreement with them to rent out her uterus in exchange for material things. This study aims to determine the Surrogate Mother validity in Indonesia and in Ukraine on born children's civil status. This study employed normative juridical methods. The findings revealed Surrogate mothers is not allowed as it against the existing law in Indonesia. This is stated in Article 127 of Law Number 36 the Year 2009, the prohibition of the surrogate mother agreement. However, if a child is born from a Surrogate Mother, his civil status will be of surrogate mother's child. In Ukraine, on the other hand, the surrogate mother is legal.  This is stated in Article 123 of the Family Code of Ukraine 2002, the children’s civil status is a genetic child of a spouse who owns the seed